Optimization of poly(vinyl alcohol-co-ethylene)-based gel polymer electrolyte containing nickel phosphate nanoparticles for dye-sensitized solar cell application - Tan, C.Y.; Omar, Fatin Saiha; Saidi, Norshahirah M.; Farhana, N.K.; Ramesh, Subramaniam; Ramesh, Kasi (Elsevier, 2019)
For the first time, metal phosphate, particularly nickel phosphate, Ni3(PO4)2 nanoparticle has been incorporated into gel polymer electrolyte (GPE) for the application in dye-sensitized solar cells (DSSCs). Poly(vinyl alcohol-co-ethylene), PVA-co-PE copolymer and sodium iodide, NaI have been employed as the host polymer and dopant salt, respectively. X-ray diffraction (XRD) studies revealed that the degree of crystallinity of the overall GPE reaches the minimum at 4 wt.% of Ni3(PO4)2 nanoparticles. The amorphous domains have boosted the mobility of the charge carriers and successfully increased the ionic conductivity from 2.27 mS cm−1 to 3.75 mS cm−1. Temperature dependence studies affirmed that the GPEs obey Arrhenius behavior in which ion hopping mechanism is dominant. This explanation was further corroborated by the results obtained from electrical modulus studies. The addition of Ni3(PO4)2 also increases both the dielectric constant and dielectric loss dramatically. Fourier transform infrared studies proved the complexation of different components found in the polymer electrolyte. Besides, the Ni3(PO4)2 nanoparticles also smoothen the morphologies of the GPE which was originally porous and rough. The efficiency of the fabricated DSSCs also nearly doubled from 3.3% to 5.8% with the incorporation of Ni3(PO4)2 nanoparticles.